2022
DOI: 10.4012/dmj.2021-253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of full and partial coverage crowns with CAD/CAM leucite reinforced ceramic blocks on fracture resistance and fractographic analysis

Abstract: To compare full and partial coverage crowns made with different CAD/CAM leucite reinforced ceramic blocks on fracture resistance and fractographic analysis. Full coverage and partial coverage crowns with finish line at 2 mm and 4 mm above the gingiva for molars made with IPS Empress CAD and Rosetta BM. After fatigue process, the fracture test and fractographic analysis were conducted. Although the fracture resistance of IPS Empress crowns did not show any statistical differences regardless of the design, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…This could be explained by the fact that full coverage retainers distribute stresses across a larger tooth crown area, transferring less strain to the abutment. [47][48][49] Concerning unilateral loading, significantly higher strain values were recorded on the loaded side when compared with the unloaded side for the three models of the study. This was consistent with other stress-strain analysis studies, in which stresses tend to be attenuated on the contralateral side of the load application, resulting in significant differences between both sides.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by the fact that full coverage retainers distribute stresses across a larger tooth crown area, transferring less strain to the abutment. [47][48][49] Concerning unilateral loading, significantly higher strain values were recorded on the loaded side when compared with the unloaded side for the three models of the study. This was consistent with other stress-strain analysis studies, in which stresses tend to be attenuated on the contralateral side of the load application, resulting in significant differences between both sides.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, dental SFRCs include short or nano fibers and inorganic filler particles as reinforcing components in a resin matrix 11) . Biomechanics assesses the mechanical responses of biological structures to forces, such as stress and deformation 12) . The biomechanics of a tooth-restoration complex are affected by a number of factors, such as forces arising in the dentition, tooth structure and morphology, and the action of elements supporting the teeth, in addition to differences between the physicomechanical properties of tooth components and of the restorative materials, and the interactions arising at the interface.…”
Section: Short Fiber Reinforcement For Resin-based Compositementioning
confidence: 99%
“…These results agreed with Alberto Jurado, et al (2022) (23) who concluded that the restorative design and material type had an effect on the fracture resistance and fracture pattern of CAD/CAM full and partial coverage crowns restorations. Also, Jurado C, et al (2022) (24) Found that CAD/CAM lithium disilicate full coverage crown in premolar has fracture resistance value greater than overlay restorations. The result shows that increasing the cusp coverage, the greater the fracture resistance of restoration.…”
Section: Table (1): Fracture Resistance Between the Three Groupsmentioning
confidence: 99%